Plant endophytes as a platform for discovery-based undergraduate science education - Strobel, S. A.; Strobel, G. A.
We have initiated an undergraduate research program that includes a two-week expedition to the Amazonian rainforest and a ten-week summer research experience. Our objective is the discovery of (i)novel microbes that are endophytically associated with plants and (ii)the potentially biologically active molecules that these microbes produce. Although the foreign travel is a strong enticement for student participation, we have found that the opportunity to own and independently direct their research program is key to program success. Intensive...
Keywords: ENDOPHYTE; MICROBIAL DIVERSITY; MICROORGANISM; MOLECULAR PHYLOGENY; MYCOBACTERIOPHAGE; NONHUMAN; PHYTOCHEMISTRY; PRIORITY JOURNAL; RAIN FOREST; REVIEW; SCIENCE